2009
DOI: 10.1074/jbc.m109.066811
|View full text |Cite
|
Sign up to set email alerts
|

Heme Ligand Binding Properties and Intradimer Interactions in the Full-length Sensor Protein Dos from Escherichia coli and Its Isolated Heme Domain

Abstract: Dos from Escherichia coli is a bacterial gas sensor protein comprising a heme-containing gas sensor domain and a phosphodiesterase catalytic domain. Using a combination of static light scattering and gel filtration experiments, we established that, as are many other sensor proteins, the full-length protein is dimeric. The full-length dimer (association constant <10 nM) is more stable than the dimeric heme domain (association constant ϳ1 M), and the dimer interface presumably includes both sensor and catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…DosP EAL was found to be dimeric by gel-filtration chromatographic analysis ( Supplementary Fig. S1), which is in line with the previously reported dimerization of full-length DosP (Lechauve et al, 2009) and other full-length EAL-domain proteins such as YkuI (Minasov et al, 2009) and BlrP1 (Barends et al, 2009). In the crystal structure of the native DosP EAL domain the dimer interface is formed mainly by interactions between a pair of antiparallel -helices (5 and 6b), which were named the compound helix and the dimerization helix, respectively, in BlrP1 (Barends et al, 2009).…”
Section: Dimerizationsupporting
confidence: 91%
“…DosP EAL was found to be dimeric by gel-filtration chromatographic analysis ( Supplementary Fig. S1), which is in line with the previously reported dimerization of full-length DosP (Lechauve et al, 2009) and other full-length EAL-domain proteins such as YkuI (Minasov et al, 2009) and BlrP1 (Barends et al, 2009). In the crystal structure of the native DosP EAL domain the dimer interface is formed mainly by interactions between a pair of antiparallel -helices (5 and 6b), which were named the compound helix and the dimerization helix, respectively, in BlrP1 (Barends et al, 2009).…”
Section: Dimerizationsupporting
confidence: 91%
“…In these proteins, oxidation, reduction, or modification of heme generally results in an alteration in protein activity. Many microbial sensor proteins have been shown to bind O 2 , NO, and/or CO via their heme group (65), which causes structural changes to the heme that ultimately regulate protein activity (13,50). NO and CO are particularly important as they are physiologically relevant and generated by human iNOS (inducible nitric oxide synthase) and HO-1 (heme oxygenase-1), respectively, as part of the protective response against microbial invasion (44) or oxidative stress (67).…”
Section: Introductionmentioning
confidence: 99%
“…Yields were between 0.5 and 1 mg/liter of culture. In order not to have to rely on standard proteins and an assumption of their conformation, we coupled SEC to multi-angle laser light scattering analysis to enable absolute molecular masses to be calculated (47). Such measurements revealed that the full-length A46 had an apparent molecular mass of 110 kDa ( Fig.…”
Section: Functional Analysis Of A46 Proteinmentioning
confidence: 99%